2013
DOI: 10.1002/elps.201200685
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization and epimerization of the aspartyl tetrapeptide Ala‐Phe‐Asp‐GlyOH at pH 10—A CE study

Abstract: Isomerization and enantiomerization of Asp in the tetrapeptide Ala-Phe-Asp-GlyOH are studied at pH 10 and 80°C as well as 25°C. CE-MS allowed the distinction between α-Asp and β-Asp linkages in degradation products based on the ratio of the b and y fragment ions. Besides isomerization and enantiomerization of Asp, enantiomerization of Ala and Phe was also observed at both temperatures by chiral amino acid HPLC analysis using Marfey's reagent for derivatization. The rate of enantiomerization of the amino acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The existence of D-isomers may be explained by racemization [22] of L-aspartic acid or epimerization of L-aspartyl residues in the polypeptides. L-Aspartic acid undergoes the fastest racemization and epimerization of the all proteinous amino acids, because particularly aspartic residue forms imide structure which fosters the epimerization [23][24][25][26]. However, if some better reaction conditions were selected, such racemization and epimerization could be minimized to be lower than 10%.…”
Section: Amino Acid Composition and D/l Ratio Of The Residue In The Hmentioning
confidence: 99%
“…The existence of D-isomers may be explained by racemization [22] of L-aspartic acid or epimerization of L-aspartyl residues in the polypeptides. L-Aspartic acid undergoes the fastest racemization and epimerization of the all proteinous amino acids, because particularly aspartic residue forms imide structure which fosters the epimerization [23][24][25][26]. However, if some better reaction conditions were selected, such racemization and epimerization could be minimized to be lower than 10%.…”
Section: Amino Acid Composition and D/l Ratio Of The Residue In The Hmentioning
confidence: 99%
“…Enantiomerization and isomerization of the Asp residue was observed under all experimental conditions. Isomerization and epimerization of another model aspartyl tetrapeptide, Ala‐Phe‐Asp‐Gly, studied at pH 10 and at 25°C and 80°C by CE‐MS under the similar experimental conditions and by chiral amino acid HPLC analysis using Marfey's reagent for derivatization has shown that the rate of enatiomerization of AAs was decreasing in the order Asp > Ala >Phe and that degradation at 25°C proceded very slowly so that the equilibrium was not reached after 245 days .…”
Section: Applicationsmentioning
confidence: 99%
“…The enantiomeric and diastereomeric CE separations of peptides were systematically investigated in Scriba's group. In addition to the above (Section ) mentioned CZE separations of isomers of degradation products of aspartyl tetrapeptides, Gly‐Phe‐Asp‐Gly , and Ala‐Phe‐Asp‐Gly , the separations of peptide diastereomers containing methionine sulfoxide were investigated by CZE with a dual‐selector system composed of achiral crown ethers (15‐crown‐5, 18‐crown‐6, Kryptofix 21®, Kryptofix 22® and CDs (β‐CD, carboxymethyl‐β‐CD, and sulfated β‐CD) at pH 2.5 and 8.0 . No separation was observed in the sole presence of crown ethers but the addition of some of them, especially the Kryptofix® diaza‐crown ethers, resulted in significantly enhaced chiral recognition, see Fig.…”
Section: Applicationsmentioning
confidence: 99%